2017
DOI: 10.1159/000477673
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intravesical Bacillus Calmette-Guérin Immunotherapy in Patients with Non-Muscle-Invasive Bladder Cancer Presenting with Asymptomatic Bacteriuria: A Systematic Review

Abstract: Intravesical Bacillus Calmette-Guérin (BCG) immunotherapy in bladder cancer patients with asymptomatic bacteriuria (ABU) remains a matter of debate. The aim of this systematic review was to present available evidence on the safety and efficacy of BCG immunotherapy in patients with ABU. A literature search within the Medline and the Embase databases was conducted with the following search terms: adverse events, bacteriuria, BCG, bladder cancer, cystitis, infection, pyuria, side effects and urinary tract infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
(21 reference statements)
0
11
0
1
Order By: Relevance
“…To reduce the risk of recurrence and Urol Int 2019;102:60-68 DOI: 10.1159/000491642 progression various strategies are proposed by literature and uro-oncological guidelines [1,5]. One of them is the restaging transurethral resection of bladder tumor (re-TURB) between primary resection (TURB) and intravesical immunotherapy [6]. However, despite the well documented reTURB position in NMIBC treatment, reTURB optimal timing remains unsettled.…”
mentioning
confidence: 99%
“…To reduce the risk of recurrence and Urol Int 2019;102:60-68 DOI: 10.1159/000491642 progression various strategies are proposed by literature and uro-oncological guidelines [1,5]. One of them is the restaging transurethral resection of bladder tumor (re-TURB) between primary resection (TURB) and intravesical immunotherapy [6]. However, despite the well documented reTURB position in NMIBC treatment, reTURB optimal timing remains unsettled.…”
mentioning
confidence: 99%
“…In this study, we found no difference between the intravesical treatment group and the no-treatment group with respect to the rate of pyuria and bacteriuria. Poletajew et al [ 20 ] have reported in their systematic review that ASBU does not negatively affect the safety and efficacy of intravesical BCG immunotherapy. The authors suggested that there is no evidence to support routine screening for and treatment of ASBU in patients scheduled for intravesical BCG instillations in those diagnosed with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, BCG is considered the standard treatment for NMIBC. However, BCG immunotherapy is associated with frequent induction of adverse effects in patients (Poletajew et al, 2017 ) leading researchers to investigate novel alternatives to increase their effectiveness (Begnini et al, 2013 ). Delivery systems and nanotechnological approaches are interesting tools to improve currently available BCG therapies and prolong exposure of the bladder tissue.…”
Section: Nano-bcg: Optimizing Bcg Immunotherapy Using Nanotechnology mentioning
confidence: 99%